Learning Clinical Ethics for Medical Students in Clinical Phase - Ismail, Taufik Suryadi; Assyifa, Shofiya; Rusnaidi, Rusnaidi (Universitas Gadjah Mada, 2024)
Background: Clinical ethics is a method of clinical decision making ethically. The implementation of clinical ethics learning to clinical rotation students is one way to help students learn to make decisions about ethical dilemmas according to the learning outcomes in clinical rotations. There is no evaluation of the implementation of clinical ethics in clinical rotation learning in our institution, so a study is needed.Methods: This research is a descriptive study with a cross-sectional design using primary data through filling out online questionnaires (g-form) adopted from four box quadrant of clinical ethics by Johnsen, Siegler and Winslade. The respondent was clinical rotation students who underwent inpatient treatment from 10 clinical rotation stages at Zainoel Abidin Hospital. This research has been done from November until December 2022 by using consecutive sampling techniques with 75 respondent as minimum sampling. Results: A total of 87 respondents were involved in this study. This study shows that clinical ethics has been implemented in clinical rotation at Zainoel Abidin Hospital Banda Aceh. The most frequent implementation of clinical ethics is Obstetrics and Gynecology, and the least common is the Psychiatric. The implementation of clinical ethics learning in clinical rotation is already good, as seen from the majority of respondents who often get learning related to the medical indications quadrant (52.9%-58.6%), patient preference quadrant (44.8%-64.4%), the quality of life quadrant (57.5%-63.2%), and the contextual features quadrant (40.2%-59.8%).Conclusion: The implementation of clinical ethics learning in clinical rotation at Zainoel Abidin Hospital Banda Aceh is already good, although not optimal. Continuous learning of clinical ethics is necessary so that clinical rotation students are accustomed to solving ethical dilemmas in clinical situations.